Development and evaluation of three mortality prediction indices for cold-stunned Kemp's ridley sea turtles (Lepidochelys kempii) - Stacy, N. I. (Conserv Physiol, 2013)
Kemp's ridley sea turtle is an endangered species found in the Gulf of Mexico and along the east coast of the USA. Cold-stunned Kemp's ridley turtles are often found stranded on beaches of Massachusetts and New York in November and December each year. When found alive, turtles are transported to rehabilitation centres for evaluation and treatment. Blood gas and chemistry analytes of major clinical relevance in sea turtles were selected to develop mortality prediction indices (MPI)s. Testing the diagnostic performance of various combinations of blood gas and chemistry analytes by receiver operating characteristics (ROC) analysis resulted in the development of three mortality prediction indices. The sensitivity and specificity of the best performing MPI (based on three blood analytes: pH, pO(2), and potassium) was 88 and 80%, respectively. Using ROC analysis, the area under the curve = 0.896 (95% confidence interval = 0.83–0.94). The use of validated MPIs based on four blood analytes (pH, pCO(2), pO(2), and potassium) could be useful for better diagnosis, treatment, and prognosis of cold-stunned sea turtles when admitted to rehabilitation facilities.